Diffusion MRI is an early biomarker of overall survival benefit in IDH wild-type recurrent glioblastoma treated with immune checkpoint inhibitors. Issue 6 (2nd December 2021) - Hagiwara, Akifumi; Oughourlian, Talia C; Cho, Nicholas S; Schlossman, Jacob; Wang, Chencai; Yao, Jingwen; Raymond, Catalina; Everson, Richard; Patel, Kunal; Mareninov, Sergey; Rodriguez, Fausto J; Salamon, Noriko; et al.
Abstract: Background: Diffusion MRI estimates of the apparent diffusion coefficient (ADC) have been shown to be useful in predicting treatment response in patients with glioblastoma (GBM), with ADC elevations indicating tumor cell death. We aimed to investigate whether the ADC values measured before and after treatment with immune checkpoint inhibitors (ICIs) and the changes in these ADC values could predict overall survival (OS) in patients with recurrent IDH wild-type GBM. Methods: Forty-four patients who met the following inclusion criteria were included in this retrospective study: (i) diagnosed with recurrent IDH wild-type GBM and treated with either pembrolizumab or nivolumab and (ii) availability of diffusion data on pre- and post-ICI MRI. Tumor volume and the median relative ADC (rADC) with respect to the normal-appearing white matter within the enhancing tumor were calculated. Results: Median OS among all patients was 8.1 months (range, 1.0–22.5 months). Log-rank test revealed that higher post-treatment rADC was associated with a significantly longer OS (median, 10.3 months for rADC ≥ 1.63 versus 6.1 months for rADC < 1.63; P = .02), whereas tumor volume, pretreatment rADC, and changes in rADC after treatment were not significantly associated with OS. Cox regression analysis revealed that post-treatment rADC significantly influenced OS ( P = .02, univariate analysis), even after controlling for age and sex ( P =.01, multivariate analysis), and additionally controlling for surgery after ICI treatment ( P = .045, multivariate analysis). Conclusions: Elevated post-treatment rADC may be an early imaging biomarker for OS benefits in GBM patients receiving ICI treatment.